Surface electromyographic characteristics of forearm muscles after ulnar and radius fracture inchildren - Qiu, Hailing; Li, Fanling; Zhang, Siqi; Xiao, Sheng; Liu, Haobo; Chen, Shuangxi; Li, Xin; Fang, Ke; Wen, Jie; Li, Tingzhi (Frontiers in Pediatrics, 2023)
Objective To evaluate the characteristics of forearm muscle activity in children with ulnar and radius fractures during different follow-up periods by surface electromyography. Methods A retrospective analysis was performed on 20 children with ulnar and radius fractures treated with an elastic intramedullary nail from October 2020 to December 2021. All children were treated with transcubital casts after surgery. At 2 months and before taking out the elastic intramedullary nail, surface electromyographic signals were collected on the flexor/extension of the wrist and the maximum arbitrary isometric contraction of the grip strength in the forearm flexor and extensor muscles of the forearm. The root-mean-square values and integrated EMG values of the superficial flexor and extensor digitalis of the healthy side and the affected side were collected at the last follow-up and 2 months after surgery, and the co-systolic ratio was calculated. The root-mean-square values and co-systolic ratio were compared and analyzed, and the Mayo wrist function score was evaluated. Results The mean follow-up time was (8.4 ± 2.85) months. Mayo scores were (87.42 ± 13.01) and (97.69 ± 4.50) points at the last follow-up and two months after surgery, respectively (p < 0.05). In the test of grip strength, 2 months after surgery, the grip strength of the affected side was lower than that of the healthy side (p < 0.05), and the maximum and mean values of the superficial flexor of the affected side were lower than those of the healthy side (p < 0.05). At the last follow-up, there was no difference in the grip strength between the affected side and the healthy side (p > 0.05), and no difference in the maximum RMS, mean RMS and cooperative contraction ratio of the superficial flexor and digital extensor muscles between the affected side and the healthy side (p > 0.05). Conclusion Satisfactory results can be obtained after elastic intramedullary napping in children with ulnar and radius fractures. However, 2 months after surgery, the grip strength of the affected side is small, and the electrical activity of the forearm muscle is low during flexion and extension activities of the wrist joint, which has not returned to normal, suggesting that children orthopaedic clinicians should remind children to conduct timely and effective rehabilitation training after the removal of the cast.